Reexamination of the A.D. 869 Jogan earthquake size from tsunami deposit distribution, simulated flow depth, and velocity. Issue 7 (1st April 2014) - Namegaya, Yuichi; Satake, Kenji
Abstract: The rupture parameters and magnitude of the A.D. 869 Jogan earthquake, a predecessor of the 2011 Tohoku earthquake, were previously estimated by matching tsunami deposit distributions with simulated inundation areas. The tsunami inundation associated with the 2011 Tohoku earthquake, however, extended farther inland than the sandy tsunami deposits. Numerical simulation of the 2011 tsunami indicated that flow depths and velocities were approximately 1 m and 0.6 m/s, respectively, at the most inland sand deposit sites on the Ishinomaki and Sendai plains. While these values depend on the assumed bottom roughness, we used these values to compare tsunami deposits and inundation simulation of the 869 Jogan earthquake from both uniform‐slip and 2011‐type variable‐slip fault models. The results showed that the rupture length of the 869 Jogan earthquake was at least 200 km and its minimum moment magnitude was 8.6. Key Points: The 2011 flow depth was at least 1 m at the most landward tsunami deposit The revised estimate of the AD 869 Jogan earthquake magnitude is at least Mw 8.6 Paleoearthquake size can be estimated from tsunami deposits and flow depth